Analisis Kinerja Karyawan PT. Pilar Indo Abadi di Surabaya - Bino Bembi Awal; Mei Retno Adiwati (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the influence of work discipline and work environment on employee performance at PT. Pillar Indo Abadi in Surabaya. The research method used is Partial Least Square (PLS). The research results show that work discipline has a positive effect on employee performance which is acceptable, with path coefficients of 0.432845, and a T-statistic value of 4.560795 which is greater than the Z value α = 0.05 (5%) = 1.96, so Significant (positive), the work environment has a positive effect on employee performance which is acceptable, with path coefficients of 0.335382, and a T-statistic value of 2.90990 which is greater than the Z value α = 0.05 (5%) = 1.96 , then it is significant (positive). In conclusion, work discipline has a positive and significant effect on employee performance at PT. Pillar Indo Abadi in Surabaya. The work environment has a positive and significant effect on employee performance at PT. Pillar Indo Abadi in Surabaya. Keywords: Work Discipline, Employee Performance, Work Environment